Future applications of fluorescence lifetime imaging ophthalmoscopy in neuro-ophthalmology, neurology, and neurodegenerative conditions - Markowitz, Daniel M.; Affel, Elizabeth; Hajnóczky, György; Sergott, Robert C. (Frontiers in Neurology, 2025)
Fluorescence lifetime imaging ophthalmoscopy (FLIO) has emerged as an innovative advancement in retinal imaging, with the potential to provide in vivo non-invasive insights into the mitochondrial metabolism of the retina. Traditional retinal imaging, such as optical coherence tomography (OCT) and fundus autofluorescence (FAF) intensity imaging, focus solely on structural changes to the retina. In contrast, FLIO provides data that may reflect retinal fluorophore activity, some of which may indicate mitochondrial metabolism. This review builds upon the existing literature to describe the principles of FLIO and established uses in retinal diseases while introducing the potential for FLIO in neurodegenerative conditions.